On a Class of Analytic Functions Defined by an Integral Operator - Pravati Sahoo; Saumya Singh (Journal of Mathematics)
We define a new subclass by using an integral operator . We find a coefficient inequality and using that we derive many sharp results. These results generalize many results which are existing in the literature.